Pemenuhan Hak Suami Dalam Kitab Dlau Al-Misbah Fi Bayani Ahkam Al-Nikah Karya Hasyim Asy’ari - Sunarto, Muhammad Zainuddin; Idhafi, Ahmad (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Husband's rights are a separate unit from several other rights and obligations that must be understood in the household. It is undeniable that households become a field of problems when husbands feel they are not getting their rights because the nature of husband's rights is not concrete and not in the form of material. However, it is more about the adab obligations of a wife. Many wives today are less concerned about their obligations. This is because the references or sources of religious knowledge are contained in large books so that not everyone can reach them. So, in the end, they are influenced by changes, some of which are contrary to the teachings of shari'a. This research has 3 objectives, namely first, knowing the fulfillment of husband's rights. Second, to know the thoughts of Hadlratus Shaykh Hasyim Asy'ari about the concept of fulfilling husband's rights. Third, to know the reality of fulfilling husband's rights from the perspective of Hadlratus Shaykh Hasyim Asy'ari in modern households. The research in this thesis uses library research (library reseach), and a character study approach. The use of personal documents as data sources, and documentation methods as data collection techniques. The results showed that the fulfillment of husband's rights was explained by Hadlratus Syaikh Hasyim Asy'ari in detail and easy to understand so that it could be used as a guide for wives who intend to get married. Among them are; 1) Obey the husband, 2) Behave well towards the husband, 3) Always ready to serve the husband, 4) Always reluctant to the husband, 5) Glorify the husband and the husband's family, 5) Keep yourself busy at home. Meanwhile, the fulfillment of husband's rights in modern households, there are things that are not in line with the thoughts of Hadlratus Syaikh Hasyim Asy'ari. Starting from a wife who is too active in the public world so that it seizes attention by not maximizing her role in the household as a wife and mother. Also the management of household assets that makes a wife a family bank, so that all financial assets or wealth are in the hands of the wife under the pretext of mere maintenance. In the end, the husband becomes limited to holding his own property.